Organizacja nadzoru nad systemem finansowym w Polsce - Kraś, Ireneusz (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2017)
Celem artykułu jest analiza działalności podmiotów nadzorujących polski system finansowy. Opracowanie rozpoczynają rozważania dotyczące istoty nadzoru nad systemem finansowym. W dalszej kolejności przedstawione są zagadnienia związane z ewolucją nadzoru finansowego w Polsce po 1989 r. Funkcjonowanie Komisji Nadzoru Finansowego jako podmiotu odpowiedzialnego za nadzór mikroostrożnościowy oraz Komitetu Stabilności Finansowej realizującego nadzór makroostrożnościowy stanowią kolejne zagadnienia opracowania. W zakończeniu autor odnosi się do przedstawionej we wstępie hipotezy i przedstawia końcowe wnioski.

The aim of this paper is to analyze the work of entities supervising the Polish financial system. It opens with considerations on the issue of supervising the financial system. Next, issues connected with the evolution of financial supervision in Poland after 1989 are presented, followed by a discussion of the functioning of the Financial Supervision Authority, as the body responsible for microprudential oversight, and the Financial Stability Committee which focuses on macroprudential oversight. Finally, the author refers to the hypothesis discussed in the introduction and presents the conclusions.
Organization of the supervision of the financial system in Poland
Keywords: system finansowy; nadzór mikroostrożnościowy; nadzór makroostrożnościowy; instytucje finansowe; financial system; microprudential oversight; macroprudential oversight; financial institutions